Prototype of an app in augmented reality for online art exhibition emphasing colorblind (Human Factors in Design, 2023)
The aim of this research was to develop a prototype app in augmented reality for online art exhibition emphasing colorblind. The theoretical concepts of this research was based on the precepts of usability, accessibility. In the first evaluation step of the interface, the interview was answered by 3 artists specialists in AR. Based on this responses, implementations were conducted in terms of for usability and accessibility. In the second evaluation step, the interview was answered by 3 colorblind people. The feedback contributed to improve online art engagement.
Keywords: augmented reality; art; usability; accessibility; colorblind; user experience